2004
DOI: 10.1186/1476-511x-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgoundPrevious studies have shown that the functional capacity of T cells may be modulated by the composition of fatty acids within, and the release of fatty acids from membrane phospholipids, particulary containing arachidonic acid (AA). The remodeling of AA within membrane phospholipids of resting and proliferating CD4+ and CD8+ T cells is examined in this study.ResultsSplenic T cells were cultured in the presence or absence of anti-CD3 mAb for 48 h then labeled with [3H]AA for 20 min. In unstimulated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 46 publications
1
10
0
3
Order By: Relevance
“…In the study by Guardamagna et al ( 7 ) , patients with family history of three or more cardiovascular events were more likely to have high Lp(a) levels, regardless of other lipid fractions. This fact could be observed in two other studies, Sáez de Lafuente et al ( 8 ) and Obisesan et al ( 10 ) , in which the family history was significantly associated with elevated Lp(a) levels. These results indicate the need for pediatricians and cardiologists' attention in order to identify and early intervene in the risk factors in children and adolescents with proven family history for CVD.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…In the study by Guardamagna et al ( 7 ) , patients with family history of three or more cardiovascular events were more likely to have high Lp(a) levels, regardless of other lipid fractions. This fact could be observed in two other studies, Sáez de Lafuente et al ( 8 ) and Obisesan et al ( 10 ) , in which the family history was significantly associated with elevated Lp(a) levels. These results indicate the need for pediatricians and cardiologists' attention in order to identify and early intervene in the risk factors in children and adolescents with proven family history for CVD.…”
Section: Discussionsupporting
confidence: 60%
“…In the study by Obisesan et al ( 10 ) , high Lp(a) levels were observed in black individuals. They have higher levels compared to other populations and the distribution is less distorted than in white individuals.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…These variations could be attributed to differences in the ratio of omega-3 long-chain fatty acids of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), depression assessment tools, intervention duration or physiological status of study participants, which varies by study. Although omega-3 DHA is recognized as an essential structural component of the cell membranes in the central nervous system [29], some evidence suggest that omega-3 EPA may be more beneficial in reduction of depression than DHA, based on its anti-inflammatory effects of the metabolic products of eicosanoids and its oxidized derivatives as well as its efficacy at reducing the inflammatory cytokines [30, 31]. These metabolic products of EPA are important in controlling the cellular inflammation in the CNS that may manifest as depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%